DOES CORRUPTION AFFECT POVERTY IN INDONESIA? - Azwar Azwar Azwar; Rahmaluddin Saragih (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2018)
Corruption is likely to increase poverty because it reduces the potential income earning of the poor. Therefore, eradicating corruption is a crucial issue in the poverty reduction process. This study is set out to investigate and analyze the short and long-run relationship between corruption and poverty. It uses secondary data from World Bank and Transparency International then Autoregressive Distributed Lag (ARDL) and dynamic Error Correction Model (ECM), focuses on capability poverty using headcount poverty index during year 1995-2017. The results of study indicated that corruption have positive significant effect on the level of poverty ratio in 1% significance level In the long run. This implies that in the long run, there is relationship between corruption and poverty. In the long run, the coefficient of corruption effect implies that 1% increase in corruption would increase the poverty ratio by 1.36%. The negative implication of corruption on the life of the citizens is a major disaster in the economy and harmful to the growth and development of the citizens in particular and the economy in general. The simple pearson correlation findings also show that corruption has significant distributional consequences by affecting growth and government expenditures. High and rising corruption increases poverty by reducing the level and effectiveness of groth and social spending (education and health). For effective sustainable and management of this disaster, government should embark on policies that will reduce the level of corruption significantly so as to have positive influence on the standard of living of the citizens in terms of quality and efficient education, sound management of our natural resources, provision of good health facilities and other infrastructures that will transcend to the growth of the economy.